Characterization and Toxicological Assessment of Iron and Zinc Nanoparticles in Male Wistar Rats - A Gamit, Martina; N Brahmbhatt, Manoj; P Bhavsar, Prakrutik; C Parmar, Bhupendra; Mankan, Mounil; B Patil, Ghanshyam (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Iron deficiency anaemia (IDA) is often studied using rat models to better understand the condition and evaluate treatment options. In this study an in vivo rat model of IDA was developed by inducing dietary iron deficiency anaemia (IDA) by offering iron-deficient diet over a period of 8-weeks to male Wistar rats as evidenced by a significant reduction in haemoglobin levels to below 9 g/dL, thereby providing a robust framework. This study explored the formulation and characterization of iron and zinc nanoparticles (100 nm and 71 nm, respectively). Adult Wistar rats (n=24) were distributed into three equal groups for treatment trial of 56 days. One group kept as control (T1) received double distilled water, while treatment groups received ionic form (T2) of 0.1 M solution each of ferric chloride hexahydrate and zinc sulphate heptahydrate, and nanoparticle forms (T3) of iron (20 mg/d) and zinc (10 mg/d) doses. Acute toxicity in the nanoparticle-treated group T3 led to 100 % mortality within 24 h with severe histopathological alterations in vital organs like liver, kidneys, spleen, heart and testes, while in ionic form T2 group subacute toxicity occurred, which was assessed over 56 days with very mild cellular changes or structures almost towards normal control group. The findings emphasized the need for cautious evaluation of zinc and iron nanoparticles in therapeutic applications.